2013
DOI: 10.1044/0161-1461(2013/12-0037)
|View full text |Cite
|
Sign up to set email alerts
|

Oral Narrative Performance of African American Prekindergartners Who Speak Nonmainstream American English

Abstract: The results are useful in interpreting the performance of African American children during the prekindergarten school year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 51 publications
5
51
3
1
Order By: Relevance
“…This result is incongruent with findings from Terry et al (2013), a study of African American preschoolers, which indicated a small inverse relationship between NMAE and three vocabulary measures: NDW (r = −.17, p < .05), PPVT-4 (r = −.29, p < .001), and Test of Preschool Early Literacy-Definitional Vocabulary (TOPEL; Lonigan, Wagner, Torgeson, & Rashotte, 2007;r = −.29, p < .001). Results of a correlational analysis indicated that there was no significant relationship between children's overall RWD and dialect variation.…”
Section: Rare-word Density Is a Dialect-neutral Measurecontrasting
confidence: 90%
See 2 more Smart Citations
“…This result is incongruent with findings from Terry et al (2013), a study of African American preschoolers, which indicated a small inverse relationship between NMAE and three vocabulary measures: NDW (r = −.17, p < .05), PPVT-4 (r = −.29, p < .001), and Test of Preschool Early Literacy-Definitional Vocabulary (TOPEL; Lonigan, Wagner, Torgeson, & Rashotte, 2007;r = −.29, p < .001). Results of a correlational analysis indicated that there was no significant relationship between children's overall RWD and dialect variation.…”
Section: Rare-word Density Is a Dialect-neutral Measurecontrasting
confidence: 90%
“…Supporting the need for considering bias in commonly used tests are studies of both African American preschoolage (Terry et al, 2013) and school-age children that have found an inverse relationship between PPVT-4 performance and NMAE production. In fact, the strength of this relationship appears to be fairly stable: Pearson product-moment correlation coefficients are small at preschool age (r = −.29, p < .001; Terry et al, 2013) and are medium at school age (r = −.31, p < .05; Mills et al, 2013).…”
Section: In Search Of An Unbiased Test Of Advanced Vocabulary For Schmentioning
confidence: 99%
See 1 more Smart Citation
“…For the present study, internal consistency for the NSS ranged from good to high (α = .77-.92) over the eight time points, with the exception of fall of kindergarten, where internal consistency was at the acceptable level (α = .63). Furthermore, the NSS was correlated with microstructure measures Terry et al, 2013), predicted a reading comprehension measure (Miller et al, 2006), and distinguished between narratives of children with disordered language and narratives of age-matched peers (Finestack et al, 2012;King et al, 2014).…”
Section: Macrostructurementioning
confidence: 97%
“…These additional features are scored holistically by examining their use throughout the entire narrative; therefore, they go beyond the specific text-level content. The NSS has proven to be a satisfactory measure of macrostructure and overall narrative quality in several recent studies using diverse groups of children, including those who were learning English (Bajaj, 2007;Finestack, Palmer, & Abbeduto, 2012;King, Dockrell, & Stuart, 2014;Miller et al, 2006;Rollins, 2014;Terry, Mills, Bingham, Mansour, & Marencin, 2013;Zhang, Anderson, & NguyenJahiel, 2013). Therefore, it was chosen for this study.…”
Section: Purpose Of the Studymentioning
confidence: 99%